ANALYSIS THE INFLUENCE OF SERVICE QUALITY CUSTOMER SATISFACTION COMMITMENT AND POWER OF RELATIONSHIP TO WORD OF MOUTH (case study at consumen car repair shop PT Persada Lampung Raya in Bandar Lampung) - Yudistira, Rizky (Jurnal Kompetitif Bisnis, 2021)
This study aims to determine analysis the influence of service quality, customer satisfaction, commitment and power of relationship to word of mouth (case study at consumen car repair shop PT Persada Lampung Raya in Bandar Lampung). This type of research is explanative research, the study population is consumen doing car repairs at car repair shop PT Persada Lampung Raya in Bandar Lampung, a sample is 97 respondent, sampling technique using non probability sampling with method accindental sampling. The analysis method used simple linear regression and multiple linear regression. The result of data analysis partially show that variable service quality, customer satisfaction, commitment and power of relationship significant effect on the word of mouth. The result of data analysis simultaneously show that all variables together significant effect on the word of mouth. Conclusion: service quality, customer satisfaction, commitment and power of relationship partially and simultaneously significant effect on the word of mouth. Keywords: service quality, service quality, customer satisfaction, commitment and power of relationship to word of mouth